The Synergy Entrepreneurial Traits And Corporate Culture on The Performance of Millenial Professionals - Rismawati, Rismawati; Setini, Made; Setena, Made; Suardana, Gede; Wahyuni, Dewi Urip (International Journal of Human Behavior Management, 2026)
Purpose – In today’s professional landscape, millennial women have become a dominant workforce group and play a crucial role in organizational performance and development. Methodology/approach – This qualitative study aims to examine how entrepreneurial traits (motivation, innovation, and creativity) and work environment factors (comfort and working conditions) influence the performance of millennial women professionals. Data were collected through in-depth interviews with five millennial women working in Bali, Indonesia. Findings – The findings indicate that entrepreneurial traits and supportive workplace conditions contribute positively and significantly to improving work performance. Motivation encourages women to stay committed, while creativity and innovation help them solve problems and adapt to professional challenges. Novelty/value – This study highlights the synergy between internal entrepreneurial behavior and external work environment support in creating competitive advantage and enhancing the productivity of millennial women in modern organizations